Who Can Reform the Labor Market? IMF Conditionality, Partisanship, and Labor Unions. Issue 5 (3rd September 2018) - Gunaydin, Hakan
ABSTRACT: Labor market reforms are critical for economic growth. Yet, they are politically contentious, and governments, more often than not, are faced with strong opposition from interest groups. Scholarly work shows that governments often rely on external intervention to implement politically difficult reforms. This is the case with the International Monetary Fund (IMF) that typically conditions its financing on the implementation of required reforms. Do borrowing governments benefit from IMF programs to overcome domestic opposition to reform by organized interests? Utilizing a unique new data set on IMF conditionality, I show that partisan and electoral concerns and domestic alliances strongly affect the implementation of labor market reforms, even when the IMF imposes them. When faced with increasing number of strikes, left-wing governments are more likely to implement labor market reforms than center/right-wing governments. However, the left is less likely than the center/right to fulfill its international commitments during election years when labor groups are militant. These findings highlight the left's unique ability to form pro-reform coalitions and the IMF's conditional role in removing domestic political opposition to reform. Counter-intuitively, right-wing governments still struggle to reform the labor market, even during economic crises and under IMF programs.